Strategi Manajemen Pendidikan Berbasis Nilai Islam Untuk Meningkatkan Mutu Hafalan Dan Karakter Santri - Yanti, Riska; Juhardi, Juhardi (Balai Diklat Keagamaan Bandung, 2025)
This study aims to examine and conceptualize the efficacy of Education Management Strategies Rooted in Islamic Values at Ma’had Ashabil Qur’an, Simeulue, Aceh, utilizing a qualitative paradigm with an instrumental case study design. Findings indicate that management is implemented through three integrated pillars: curriculum development, systematic instructional practices (murājaʿah), and pesantren culture reinforcement (uswah). Islamic principles drive managerial decisions, enhancing memorization and character development. Conceptually, this system yields the Qur'anic Integral Management Model, where spiritual integrity is the highest success indicator. The substantial scholarly contribution is an empirical demonstration that fundamentally reformulates Maslow's theory and quality management principles, showing that basic needs imbued with Islamic values are a necessary theological prerequisite for achieving Islamic self actualization.